A scoping review to map the evidence of physical activity interventions in post-treatment adolescent and young adult cancer survivors. (March 2022) - Caru, Maxime; Levesque, Ariane; Rao, Pooja; Dandekar, Smita; Terry, Christopher; Brown, Valerie; McGregor, Lisa; Schmitz, Kathryn
Graphical abstract: Highlights: This review maps the current evidence of physical activity interventions in adolescents and young adult cancer survivors. The findings highlight the paucity of data in this area of investigation, obviating how much work remains to be done. Future studies are necessary to demonstrate the potential benefits of physical activity on adolescents and young adult cancer survivors' health outcomes. This review describes and synthesizes previously reported data to map the current evidence. This review contributes to the development of new clinical and research perspectives. Abstract: Purpose: This scoping review describes and synthesizes previously reported data to document physical activity (PA) interventions in adolescents and young adult (AYA) cancer survivors and to explore whether PA interventions tested to date improve survivors' health outcomes. Methods: A search of the literature was conducted in PubMed, CINAHL, EMBASE, Web of Science and Cochrane Library following the PRISMA-ScR statement. We included all original studies (n = 8) investigating PA interventions in AYA cancer survivors. Results: This review showed that PA interventions were feasible and acceptable in AYA cancer survivors. PA interventions were individualized and mainly aerobic in nature. Studies examining the effects of PA interventions on survivors' health evaluated physical and mental health outcomes. Conclusions: Our scoping review maps the current evidence of PA interventions and highlights the paucity of data in this area of investigation, obviating how much work remains to be done to demonstrate the potential benefits of PA on AYA cancer survivors' health outcomes.